IDENTIFYING CHARACTERS OF JAVANESE COMEDY KUNTET EDAN BY LUDRUK BUDHI WIJAYA - Ernawati, Luluk; Hanifa, Siti (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
ABSTRACT Drama in the world of literature is a form of literary work that provides an overview of human life through dialogues, actions, and emotions. The topic of this research is characters and characterizations in the Javanese Comedy Kuntet Edan. The objective of the study is to identify the types of characters and characterization in this Javanese Comedy. The writer focuses on all characters in this Javanese Comedy. The method in this study is a descriptive qualitative method, the object and the source of the data of this study is the Javanese Comedy entitled Kuntet Edan by Ludruk Budhi Wijaya, which was performed in 2017. The writer uses the theory of New Criticism focusing on intrinsic elements, e.g., character and characterization. The data of this study are the characters’ utterances and actions. This study found that the characters of the Javanese Comedy are categorized as flat, round or dynamic, and protagonist. Next, the types of characterization include (1) direct, and (2) indirect characterization. Keywords: Characters, Characterization, New Criticism, Javanese Comedy ABSTRAK Drama dalam dunia sastra merupakan salah satu bentuk karya sastra yang memberikan gambaran tentang kehidupan manusia melalui dialog, tindakan, dan emosi. Topik penelitian ini adalah tokoh dan penokohan dalam Komedi Jawa Kuntet Edan. Tujuan dari penelitian ini adalah untuk mengidentifikasi tipe-tipe tokoh dan penokohan dalam Komedi Jawa ini. Penulis memfokuskan pada semua karakter dalam Komedi Jawa ini. Metode dalam penelitian ini adalah metode deskriptif kualitatif, objek dan sumber data penelitian ini adalah Komedi Jawa berjudul Kuntet Edan karya Ludruk Budhi Wijaya yang dipentaskan pada tahun 2017. Penulis menggunakan teori Kritik Baru dengan fokus pada unsur intrinsik, misalnya karakter dan penokohan. Data dari penelitian ini adalah ucapan dan tindakan para tokoh. Penelitian ini menemukan bahwa karakter dalam Komedi Jawa dikategorikan datar, bulat atau dinamis, dan protagonis. Selanjutnya, jenis-jenis penokohan meliputi (1) penokohan langsung, dan (2) penokohan tidak langsung. Kata kunci: Tokoh, Penokohan, Kritik Baru, Komedi Jawa